2021
DOI: 10.37287/jppp.v3i2.481
|View full text |Cite
|
Sign up to set email alerts
|

Peran Keluarga Berhubungan dengan Kepatuhan Minum Obat Klien Tuberkulosis

Abstract: Tuberkulosis aru merupakan penyakit menular yang saat ini telah menjadi ancaman global, karena hampir sepertiga penduduk dunia telah terinfeksi. Indonesia menempati posisi ketiga dunia untuk banyaknya penderita penyakit tuberculosis. Tingginya angka kematian yang disebabkan oleh tuberculosis paru, salah satu penyebabnya yaitu kurangnya kepatuhan dalam konsumsi obat. Dalam hal ini peran keluarga sangat dibutuhkan untuk mengawasi kepatuhan pasien tuberculosis paru dalam mengkonsumsi obat. Penelitian ini bertujua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The results of statistical analysis using the Chi-square test showed that the value of p (0.042) > 0.05, which means there is a relationship between the role of family support and compliance with pulmonary tuberculosis client medication (table 2). This study's results align with research conducted by Lestari, which states that there is a very strong relationship between the family's role and adherence to medication in tuberculosis clients 9 . This research is also in line with Nurhidayati's research, which said that there was a relationship between the role of the family and adherence to taking medication in patients with pulmonary tuberculosis in Kawedanan Pedan with a p-value = 0.000 with Kendall Tau's statistic 15 .…”
Section: Analysis Of the Relationship Between Family Roles And Client...supporting
confidence: 88%
See 2 more Smart Citations
“…The results of statistical analysis using the Chi-square test showed that the value of p (0.042) > 0.05, which means there is a relationship between the role of family support and compliance with pulmonary tuberculosis client medication (table 2). This study's results align with research conducted by Lestari, which states that there is a very strong relationship between the family's role and adherence to medication in tuberculosis clients 9 . This research is also in line with Nurhidayati's research, which said that there was a relationship between the role of the family and adherence to taking medication in patients with pulmonary tuberculosis in Kawedanan Pedan with a p-value = 0.000 with Kendall Tau's statistic 15 .…”
Section: Analysis Of the Relationship Between Family Roles And Client...supporting
confidence: 88%
“…In supervising the regularity of taking medication for pulmonary TB sufferers, the important role of the family is needed as the closest unit to the patient. Part of the family is by family's duties in the health sector one of which is providing care to family members who are sick and unable to help themselves due to disabilities or too young age; for example, the family reminds/monitors the time to take medication, controls drug supplies, takes patients controls 9 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation